A task for laser cutting of lamellae with TruLaser 1030 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The growing development of manufacturing, automotive, aerospace and other sectors in the industry generates the necessity to continuously expanding on modifications of electrical machinery and equipments which are used in them, as well as to improve their performance and reliability. The report presents some results from a study to the process of laser cutting through melting on lamellae for rotor and stator packages by using the laser system TruLaser 1030. Some functional dependencies are offered between physical quantities describing the cutting process by melting and technological parameters aimed providing the quality requirements. With a software TruTops to optimize the cutting out are shown the results of studies to determine the technological working time for cutting of a concrete stator lamella.